Communication, dialogue and project management. Issue 4 (7th September 2015) - Ziek, Paul; Anderson, J. Dwight
Abstract : Purpose: – Project communication is overwhelmingly viewed as the proper and timely delivery of pertinent project information. The view of communication in this way misses the constitutive nature of communication. Communication is more than message exchange but a way that project managers generate the grounds for a project. The purpose of this paper is to explore how the communicative practices of project managers creates a dialogue with stakeholders that ultimately impacts the content, direction and outcome of a project. Design/methodology/approach: – Semi-structured interviews were performed with project managers from the Project Management Office of a large international bank. The project managers were responsible for their own projects of varying size with scopes that included everything from marketing initiatives to heavily oriented technology projects. Findings: – Overall, the project managers interviewed for the current project do not subscribe to the belief that communication is part of a constitutive dialogue. Instead, when discussing their overall views of communication, 82 percent of the interviewees took a transmission approach to the action. To that end, they believe that the goal of communication is to send clear, unambiguous and complete information. Originality/value: – Unlike other studies about communication within the field of project management, the current study looks to uncover how communication is part of a constitutive dialogue between a project manager and project stakeholders. The researchers did not look just to understand the micro-level exchanges between project managers and stakeholders but how those exchanges enabled a sustained dialogue that shapes the scope and trajectory of a project.